Fuzzy Fixed Point Results of Fuzzy Mappings on b-Metric Spaces via α∗, F-Contractions. (29th July 2022) - Batul, Samina; Sagheer, Dur-e-Shehwar; Anwar, Muhammad; Aydi, Hassen; Parvaneh, Vahid
Abstract : In this manuscript, we establish some fixed point results for fuzzy mappings via α ∗, F -contractions. For validation of the proved results, some nontrivial examples are presented. Few interesting consequences are also stated which authenticate that our results generalize many existing ones in the literature.